2022
DOI: 10.1186/s12877-022-03064-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of textured food masticatory performance in older people with different dental conditions

Abstract: Background Physiological deterioration (aging, poor dental status, and reduced tongue pressure) makes chewing difficult. This study aimed to investigate the chewing patterns of older people with or without dentures, evaluate the textural and masticatory properties of texture-modified radish Kimchi, and investigate the correlation between dental status and tongue pressure. Additionally, differences in the subjective–objective concordance of texture-modified Kimchi were investigated using the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
10
0
2
Order By: Relevance
“…75 Electromyographic (EMG) recordings were also commonly preferred. 18,26,27,53,77 This test was performed by placing electrodes on masseter and temporalis muscles for which signals were recorded during chewing cycles or maximum contractions. 26 Other less common methods included the swallowing threshold test, tongue pressure and oral diadochokinesis.…”
Section: Measures Of Masticatory Performancementioning
confidence: 99%
See 2 more Smart Citations
“…75 Electromyographic (EMG) recordings were also commonly preferred. 18,26,27,53,77 This test was performed by placing electrodes on masseter and temporalis muscles for which signals were recorded during chewing cycles or maximum contractions. 26 Other less common methods included the swallowing threshold test, tongue pressure and oral diadochokinesis.…”
Section: Measures Of Masticatory Performancementioning
confidence: 99%
“…82 Malnutrition, while being a risk factor, was primarily noted as a consequence of masticatory dysfunction. 11 Some studies revealed that the type of food consumed may be a risk factor to masticatory dysfunction in situations where subjects ate softer diets or consumed less folic acid and vitamin A 22,77,83 ; however, regarding the nutrition category, the scoping review predominantly showed that masticatory dysfunction lead to a nutrient-deficient diet and consequently caused disturbances in general health. 84 Therefore, this scoping review revealed the bidirectional risk factor connection between nutrition and masticatory performance.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Older people are more likely to consume insufficient amounts of food and dietary nutrients because of their reduced basal metabolic rates [ 3 ], chewing and swallowing impairment [ 4 ], swallowing [ 5 ], digestion and absorption capacities [ 6 ] and lower levels of physical activity [ 7 ]. Malnutrition in older adults can lead to several adverse clinical outcomes, such as increased disability, morbidities, mortality rate and deteriorated quality of life [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…On top of that, poor oral health makes chewing difficult, limits food choices, and diminishes the pleasures of eating. 22 Particularly, extensive tooth loss in older persons impairs chewing efficiency. 23,24 In consequence, oral health in older adults is interrelated to malnutrition, anorexia, food neophobia, and obesity.…”
mentioning
confidence: 99%